Дослідження стоянки Вись у 2009, 2010 роках та її місце у пізньому палеоліті України - Залізняк, Л.Л.; Беленко, М.М.; Федорченко, О.С.; Нездолій, О.І.; Озеров, П.І. (Кам’яна доба України, 2010)
Стаття присвячена публікації та культурно-історичній інтерпретації нових матеріалів з розкопок 2009-2010 рр. стоянки селетського технокомплексу Вись, яка знаходиться біля райцентру Новомиргород у Центральній Україні. Article is devoted to publication and cultural and historical interpretations of new material from excavations of 2009-2010 at the site of Vys’ that belongs to Szeletian technocomplex and localized next to the district center of Novomyrhorod in central Ukraine. Along with triangular bifacial points of Streletskaya type assemblage includes numerous high endscrapers inherent to Aurignacian sites of Early Upper Palaeolithic.